Kierunki zarządzania wiedzą. Nowe formy organizacji oparte na wiedzy - Mirowski, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
There is a link between effective knowledge management and the increase of company shareholder value. New forms of knowledge-based organizations tend to be more flexible than hierarchical ones and to out-perform their competitors during economy slowdowns.
Keywords: zarządzanie wiedzą; organizacje; wiedza